Synchrony as an Adaptive Mechanism for Large‐Scale Human Social Bonding. (29th August 2016) - Launay, Jacques; Tarr, Bronwyn; Dunbar, Robin I. M.
Abstract: Humans have developed a number of specific mechanisms that allow us to maintain much larger social networks than would be expected given our brain size. For our primate cousins, social bonding is primarily supported using grooming, and the bonding effect this produces is primarily mechanistically underpinned by the release of endorphins (although other neurohormones are also likely to be involved). Given large group sizes and time budgeting constraints, grooming is not viable as the primary social bonding mechanism in humans. Instead, during our evolutionary history, we developed other behaviours that helped us to feel connected to our social communities. Here, we propose that synchrony might act as direct means to encourage group cohesion by causing the release of neurohormones that influence social bonding. By acting on ancient neurochemical bonding mechanisms, synchrony can act as a primal and direct social bonding agent, and this might explain its recurrence throughout diverse human cultures and contexts (e.g. dance, prayer, marching, music‐making). Recent evidence supports the theory that endorphins are released during synchronised human activities, including sport, but particularly during musical interaction. Thus, synchrony‐based activities are likely to have developed due to the fact that they allow the release of these hormones in large‐scale human communities, providing an alternative to social bonding mechanisms such as grooming.